A methodological tool for characterizing the therapeutic acts of animal-assisted therapy - Arni Zacks; Oran Nitsani (Human-Animal Interactions, 2025)
Abstract Animal-assisted psychotherapy (AAT) has established itself as a unique therapeutic method that combines dynamic interactions between humans and animals to promote clients’ goals, while promoting the well-being of the animals. This study aimed to identify and characterize the distinctive components of AAT therapeutic practice. The study used a qualitative analysis of 140-therapy session diary entries, applying the principles of Consensus Qualitative Research (CQR). We categorized the findings into five main content areas: verbal interaction, interactions with animals, physical activity, active creative expression through play, and emotional expression. We created a prevalence table according to a representative sample across diverse settings and populations. It may serve as a standard, a basis for comparison. This methodological tool is easy to use; meeting reports can be compared to check the needs of an individual or population. What a particular therapeutic setting allows. It is possible to direct certain goals to an appropriate therapeutic setting. The findings underscore the complex and unique dynamics of AAT, which relies on the triangular relationship between therapist, client, and animal, creating a multidimensional therapeutic space that offers unique opportunities to enhance emotional and social functioning. With the help of the information from this study, we can refine the curriculum for students on the diversity of psychotherapeutic methods and animal welfare.